2018
DOI: 10.1037/pha0000192
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette and e-liquid demand and substitution in e-cigarette-naïve smokers.

Abstract: Behavioral economic methods allow experimental manipulation of price and examination of its effects on tobacco product purchasing. These methods may be used to examine tobacco product abuse liability and to prospectively model possible effects of price regulation. In the present study, we examined multiple measures of behavioral economic demand for cigarettes and e-liquid for use in a second-generation electronic cigarette (e-cigarette) in e-cigarette-naïve cigarette smokers. Twenty-five smokers received an e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
3
30
0
3
Order By: Relevance
“…To date, much of the literature on behavioral economic interactions among drug reinforcers has examined demand for cigarettes and alternative nicotine products (Grace et al., ; Johnson et al., ; Stein et al., ), with some recent applications to cannabis (Amlung et al., ). For example, e‐cigarettes were found to substitute for real cigarettes in hypothetical and experimental purchase tasks administered to smokers (Grace et al., ; Johnson et al., ; Stein et al., ), and Amlung and colleagues () found that legal and illegal cannabis substituted for each other in a cannabis purchase task. These results regarding the behavioral economics of nicotine and cannabis indicate that demand for commonly used drugs can be decreased in the presence of lower‐priced alternatives.…”
mentioning
confidence: 99%
“…To date, much of the literature on behavioral economic interactions among drug reinforcers has examined demand for cigarettes and alternative nicotine products (Grace et al., ; Johnson et al., ; Stein et al., ), with some recent applications to cannabis (Amlung et al., ). For example, e‐cigarettes were found to substitute for real cigarettes in hypothetical and experimental purchase tasks administered to smokers (Grace et al., ; Johnson et al., ; Stein et al., ), and Amlung and colleagues () found that legal and illegal cannabis substituted for each other in a cannabis purchase task. These results regarding the behavioral economics of nicotine and cannabis indicate that demand for commonly used drugs can be decreased in the presence of lower‐priced alternatives.…”
mentioning
confidence: 99%
“…Upon completion of this research, another report was published on e‐cigarette naïve individuals showing an asymmetric substitution pattern in which e‐liquid (24 mg/ml) served as a partial substitute for combustible cigarettes but not the reverse. Additionally, the participants in that study valued e‐liquid positively and purchased it frequently both as a substitute for and independently of combustible cigarettes …”
Section: Resultsmentioning
confidence: 99%
“…Elasticity estimates (non‐transformed means across vaping status groups ranged from 0.031 to 0.035 for daily smokers and 0.059 to 0.094 for non‐daily smokers) were comparable to prior studies , but testing demand in the context of other substitutable products provides a more realistic assessment of how consumers make product choices. Further study might apply methods that allow for the measurement of cross‐price elasticity, a direct test of product substitutability and a more robust test of the probable impact of having alternative products available to consumers at different price points .…”
Section: Discussionmentioning
confidence: 99%